An analysis of the impact that false cognates have in the reading comprehension skills of second semester students in the modern languages program at the University of Quindío (2017)
False cognates are understood as those groups of words equal or similar in form in two languages but have different etymologies and different meanings. This phenomena becomes as real problem for language learners. The transfers of L1 words can affect the learner’s communicative skills if they are not prepared in a special way for detecting this kind of words. Therefore, the present study aims at analyzing the difficulties learners have when it comes to use these words. Likewise, it is intended to shed light in the impact that False Cognates have in the reading comprehension skill of second semester students in the Modern Languages Program at the University of Quindío. In all probability, the conclusions of this study will provide new insights into this phenomenon and establish the influence that False Cognates have in the reading comprehension skill.